2014
DOI: 10.1371/journal.pone.0108165
|View full text |Cite
|
Sign up to set email alerts
|

Role of Key TYMS Polymorphisms on Methotrexate Therapeutic Outcome in Portuguese Rheumatoid Arthritis Patients

Abstract: BackgroundTherapeutic outcome of rheumatoid arthritis (RA) patients treated with methotrexate (MTX) can be modulated by thymidylate synthase (TS) levels, which may be altered by genetic polymorphisms in TS gene (TYMS). This study aims to elucidate the influence of TYMS polymorphisms in MTX therapeutic outcome (regarding both clinical response and toxicity) in Portuguese RA patients.MethodsClinicopathological data from 233 Caucasian RA patients treated with MTX were collected, outcomes were defined and patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 39 publications
2
18
0
Order By: Relevance
“…Thus, in a recent study of Caucasian RA patients, the frequency of the TYMS 2R allele has been reported to be 0.41 [52] and we found a frequency of 0.63 in our study. The discordance between the results could also be explained by the variation of TYMS gene copy number due to loss of heterozygosis or gene amplification as reported by Uchida et al (2004) in patients with colorectal cancer treated by 5-fluorouracilbased therapy [53].…”
Section: Discussionsupporting
confidence: 76%
“…Thus, in a recent study of Caucasian RA patients, the frequency of the TYMS 2R allele has been reported to be 0.41 [52] and we found a frequency of 0.63 in our study. The discordance between the results could also be explained by the variation of TYMS gene copy number due to loss of heterozygosis or gene amplification as reported by Uchida et al (2004) in patients with colorectal cancer treated by 5-fluorouracilbased therapy [53].…”
Section: Discussionsupporting
confidence: 76%
“…In addition, the 3R/3R genotype among patients with the TYMS 5′-UTR 28-bp tandem repeat was associated with a better MTX therapeutic response than the 2R allele, although the difference was not slightly significant. The same tendency was found by James et al, 44) but the opposite result was reported by Lima et al 45) For the TYMS 5′-UTR 28-bp tandem repeat, it was reported that 3R compared with 2R increased the level of mRNA expression, 46,47) and MTX dosage increases in patients with the 3R allele achieved the same therapeutic effect as in those without 3R allele. 48) However, this study did not examine differences in the MTX dose required among TYMS 5′-UTR genotypes.…”
Section: Discussionsupporting
confidence: 72%
“…The allele with two repeats (2R) has been shown to cause decreased translation of TYMS relative to the three-repeat (3R) allele [55], but the exact mechanism is not fully known. It has been reported that patients with rheumatoid arthritis and TYMS 3R3R genotype show a weaker response to MTX therapy [56]. The 3 UTR region of the TYMS gene contains and 6bp-long indel.…”
Section: Discussionmentioning
confidence: 99%